New perspectives in international business research - Feldman, Maryann P.; Santangelo, Grazia D., 1973- (JAI Press, 2008)
This volume of "Progress in International Business Research" proposes new perspectives in IB research by addressing a number of critical issues which criss-cross the fields of International Business and International Management. More specifically, the topics dealt with in the volume feature in four discreet sections. The contributions in the first part concern the management of cultural distance across countries. In the second part, internal and external solutions to corporate governance problems are proposed, making use of the concept of 'jurisdictional advantage'. The third part focuses on the genesis and development of international entrepreneurs. The last part of the volume discusses the nature and impact of technology and of international expansion.The volume intends to provide fresh new insights in the field of IB research, insights which will interest business and management scholars, senior executives and policy-makers, and all those interested in the relationship and combination of corporate competitive advantage with jurisdictional advantage.
Keywords: Business -- Research.; International business enterprises -- Management.; elektronické knihy; electronic books